Evalution of Intubating Conditions and Cardiovascular Effects of Rocuronium, Suxamethanium and Vecuronium - Roseline Zohra Ali; Parvez Akhtar; Priyadershini Rangari (Academia Anesthesiologica International, 2019)
Background: Provision of muscle relaxation for endotracheal intubation demands a relatively safer drug than suxamethonium, which can provide good intubating conditions as early as possible with minimal side effects and stable haemodynamic profile.Objectives:The present study aimed at evaluating the intubating condition and cardiovascular effects of rocuronium and compares it with suxamethonium and vecuronium. Subjects and Methods: The study was conducted on 120 patients divided randomly into three groups of forty each, on the basis of muscle relaxant used for tracheal intubation as Group A with rocuronium, 0.6 mg/kg, Group B with suxamethonium, 1.5 mg/kg and Group C with vecuronium, 0.08 mg/kg.All the patients were premedicated with 0.2 mg glycopyrrolate and anaesthesia was induced by thiopentone sodium 2.5%, 4-5 mg/kg given intravenously then maintained on N20: 02 mixture (66.6% & 33.3%) and intermitted injection of vecuronium. Parameters were observed like onset of apnoea, jaw relaxation, vocal cord position, vocal cord movement, coughing, limb movement cardiovascular response and fasciculations.Results: Onset of action in Group A slightly longer than Group B but far shorter than Group C.Fasiculations was absent with both Group A and C but was present with Group C. Intubating condtions were better after Group C. None of the patients developed complication of any type during the procedure. Conclusion: It is thus concluded from the above study that rocuronium can very well subsitutesuxamethonium for tracheal intubation when a rapid return to spontaneous respiration is not desired. It thus fills the gap between suxamenthonium and non-depolarizing neuromuscular blocking agents and is a step ahead in search for an ideal neuromuscular blocking drug.